Mathematical Model of Electric Field Distribution at a Critical State in Bubble Electrospinning (Journal of Fiber Bioengineering and Informatics, 2018)
Bubble electrospinning is a novel method to produce ultrafine nanofibers. In this work, amathematical model of the electric field distribution in a critical state was established for bubbleelectrospinning process and was numerically simulated using finite element method. The results indicatedthat the maximum electric force occurred at the tip of the bubble, it is probably for this reason that the firstjet occurs at the tip of the bubble, when the electrical force exceeds the surface tension, which also possiblyinduces bubble bursting.